1976
DOI: 10.1084/jem.144.5.1305
|View full text |Cite
|
Sign up to set email alerts
|

Role of interferon in the pathogenesis of virus diseases in mice as demonstrated by the use of anti-interferon serum. I. Rapid evolution of encephalomyocarditis virus infection.

Abstract: The role of interferon in the pathogenesis of encephalomyocarditis (EMC) virus infection was determined by treating mice with potent, partially purified sheep anti-mouse interferon globulin. In control mice, EMC virus was present in low titers in various visceral organs but attained high titers in the brain towards the 4th to 5th day, at which time mice died with signs of central nervous system disease. In mice treated with anti-mouse interferon globulin, virus was present in high titer in visceral organs 24--… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
0

Year Published

1980
1980
2008
2008

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 248 publications
(87 citation statements)
references
References 5 publications
5
82
0
Order By: Relevance
“…The growthinhibitory effect was not due to cell death in these experimental conditions (data not shown). We have verified that the lower virus production in serum-free medium as compared to medium containing serum is not due to a low spontaneous production of interferon by using antiinterferon antibodies (Gresser et al, 1976) (data not shown). Our results do not contradict previous reports on different serum-dependent cellular systems which have firstly pointed out that removal of serum increases the inhibition of cell growth by interferon (Gresser et al, 1970;Kading et al, 1978;Tovey & Brouty-Boy6, 1979) and secondly demonstrated that growth factors antagonize the inhibitory effect of interferon on cell growth and virus production (Lin et al, 1980;Oleszak & Inglot, 1980;Pfeffer et al, 1980;Taylor-Papadimitriou, et al, 1981).…”
Section: Oomentioning
confidence: 74%
“…The growthinhibitory effect was not due to cell death in these experimental conditions (data not shown). We have verified that the lower virus production in serum-free medium as compared to medium containing serum is not due to a low spontaneous production of interferon by using antiinterferon antibodies (Gresser et al, 1976) (data not shown). Our results do not contradict previous reports on different serum-dependent cellular systems which have firstly pointed out that removal of serum increases the inhibition of cell growth by interferon (Gresser et al, 1970;Kading et al, 1978;Tovey & Brouty-Boy6, 1979) and secondly demonstrated that growth factors antagonize the inhibitory effect of interferon on cell growth and virus production (Lin et al, 1980;Oleszak & Inglot, 1980;Pfeffer et al, 1980;Taylor-Papadimitriou, et al, 1981).…”
Section: Oomentioning
confidence: 74%
“…The origin, purification, and assay of IFN-␣␤ neutralizing sheep Ig (anti-IFN-␣␤) and matching normal sheep Ig have been previously described in detail (21,22). Control sheep IgG or anti-IFN-␣␤ was delivered as described (23).…”
Section: In Vivo Ifn-␣␤ Blockadementioning
confidence: 99%
“…These and the isotype control mAbs were obtained in our laboratory from hybridoma supernatants and isolated by protein G affinity chromatography. The neutralizing anti-IFN-␣␤ Ab was a sheep anti-mouse IFN-␣␤ antiserum titrated by I. Gresser (Centre de Recherches Biomedicales des Cordeliers, Université Pierre et Marie Curie, Paris, France) for its potency to neutralize the inhibitory activity of IFN-I in a viral neutralizing assay; it was used at a dilution that neutralized 2000 U of IFN-I/ml (31). Isotype control rat anti-␤-galactosidase GL113 (IgG1) and GL117 (IgG2a) mAbs or sheep serum anti-mouse L cells (G-025-501-568 National Institute of Allergy and Infectious Diseases repository, National Institutes of Health) were used as controls for the anti-cytokine Ab treatments.…”
Section: Cell Culturesmentioning
confidence: 99%